1994
DOI: 10.1029/93jb03403
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of subducted oceanic crust in the convecting mantle

Abstract: Subducted oceanic crust, transformed into dense mineral assemblages at high pressure, may gravitationally segregate at the bottom of the convecting mantle, for example, the D″ layer. Here it could be stored for a long enough time to develop an “enriched” isotopic signature, before it is recycled in mantle plumes and hence control the geochemical character of hot‐spot basalts. We study both the geodynamical and geochemical aspects of this hypothesis in two‐dimensional numerical convection models, in which plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
505
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(540 citation statements)
references
References 64 publications
33
505
2
Order By: Relevance
“…Solomatov & Stevenson 1993;Labrosse et al 2007;Lee et al 2010;Tolstikhin et al 2006), or from accumulation of subducted oceanic crust above the core-mantle boundary (CMB, e.g. Gurnis & Davies 1986;Christensen 1989;Christensen & Hofmann 1994). Recently, it was proposed that small fractions of recycled mid-ocean ridge basalt (MORB) may be episodically incorporated in pre-existing primordial reservoirs (Tackley 2012), which is supported by high-resolution 2-D Cartesian models of convection (Li et al 2014).…”
Section: Introductionmentioning
confidence: 92%
“…Solomatov & Stevenson 1993;Labrosse et al 2007;Lee et al 2010;Tolstikhin et al 2006), or from accumulation of subducted oceanic crust above the core-mantle boundary (CMB, e.g. Gurnis & Davies 1986;Christensen 1989;Christensen & Hofmann 1994). Recently, it was proposed that small fractions of recycled mid-ocean ridge basalt (MORB) may be episodically incorporated in pre-existing primordial reservoirs (Tackley 2012), which is supported by high-resolution 2-D Cartesian models of convection (Li et al 2014).…”
Section: Introductionmentioning
confidence: 92%
“…Gonnerman et al (2002) showed that even if the initial layer is stable, entrainment of material would progressively decrease the density contrast and lead to a present unstable layer. Second, slabs may penetrate in the lower mantle and reach the CMB, where they sediment in pools (e.g., Christensen and Hofmann, 1994). Again, the density contrast and quantity of sinking material should not be too large to allow the development of instabilities.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of experimental (Olson and Kincaid, 1991;Davaille, 1999) and numerical (Hansen and Yuen, 1988;Christensen and Hofmann, 1994;Kellogg et al, 1999;Tackley, 1998Tackley, , 2002Schott and Yuen, 2004) models of thermo-chemical convection have been developed, showing strong stratification or a more complex structure, depending on the fluid properties and on the buoyancy ratio. A major improvement was to perform calculations that account for fluid compressibility, either using the anelastic (Tackley, 1998), or extended Boussinesq (Schott and Yuen, 2004) approximation.…”
Section: Density Anomalies From Thermo-chemical Convectionmentioning
confidence: 99%
“…[10] Other models by Christensen and Hofmann [1994], Sidorin and Gurnis [1998], and Davies [2002] yield considerably thinner layers that are different from the main part of the mantle with respect to major element distribution and correspond to the D 00 layer that develops from subducted oceanic crust. Davies' [2006] results show only a very thin dense layer at the base of the mantle.…”
Section: Chemical Differentiationmentioning
confidence: 99%